Cerebral Blood Flow During Treadmill Exercise Is a Marker of Physiological Postconcussion Syndrome in Female Athletes. Issue 3 (May 2016) - Clausen, Mary; Pendergast, David R.; Willer, Barry; Leddy, John
Abstract : Objective: Some patients with postconcussion syndrome (PCS) have reduced exercise capacity that may reflect altered central cardiorespiratory control. The purpose of this study was to evaluate control of cerebral blood flow (CBF) during exercise in females with PCS. Setting: University Concussion Clinic. Participants: Nine female Division 1 collegiate team athletes with PCS (23 ± 6 years) and a reference group of 13 healthy female recreational aerobic athletes (21 ± 3 years). Design: A prospective experimental study. All PCS athletes were compared with the reference group at the beginning of the study. Six of the PCS athletes were subsequently measured before and after a subsymptom threshold aerobic exercise treatment program. Main Measures: Exercise treadmill test during which blood pressure (BP), minute ventilation ( E), end-tidal CO2 (PETCO2 ), and CBF velocity (CBFV, by transcranial Doppler) were measured. Results: Participants with PCS had significantly lower E (by 18%) and greater PETCO2 (5%) and CBFV (14%) versus the reference group at similar workloads in association with appearance of symptoms and premature exercise cessation. Subthreshold exercise normalized E, PETCO2, CBFV and exercise tolerance. Before treatment, PCS had low CO2 sensitivity that blunted their exercise ventilation. CO2 sensitivity and ventilation improved after exercise treatment. Conclusion: Some PCS patients have exercise intolerance due to abnormal CBF regulation that may be the result of concussion-induced altered sensitivity to CO2 . Return of normal CBF control and exercise tolerance may be physiological markers of recovery from concussion. Abstract : Supplemental Digital Content is Available in the Text.